2010
DOI: 10.4103/0973-1482.77101
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia with radiation in the treatment of locally advanced head and neck cancer: A report of randomized trial

Abstract: Radiofrequency (RF) based heating and radical radiation of head and neck cancers is better than in RT alone group. HT should be considered as a valid option wherever the facility for HT is available. This report should infuse greater confidence in radiation Oncologists to practice HT as an adjuvant treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 10 publications
0
66
0
5
Order By: Relevance
“…Survival was also significantly increased on the hyperthermia arm to 8.0 months as compared to 4.8 months with radiation alone. (80) Notably, chemotherapy and IMRT were not utilized, a significant number of patients in both arms did not complete the intended treatment or were lost to follow-up, and overall outcomes were worse than expected with optimal standard therapy, therefore limiting the conclusions that can be drawn from this study. Never-the-less overall these head and neck trials indicate there is significant potential for hyperthermia to improve outcomes for head and neck malignances.…”
Section: Head and Neck Cancermentioning
confidence: 97%
“…Survival was also significantly increased on the hyperthermia arm to 8.0 months as compared to 4.8 months with radiation alone. (80) Notably, chemotherapy and IMRT were not utilized, a significant number of patients in both arms did not complete the intended treatment or were lost to follow-up, and overall outcomes were worse than expected with optimal standard therapy, therefore limiting the conclusions that can be drawn from this study. Never-the-less overall these head and neck trials indicate there is significant potential for hyperthermia to improve outcomes for head and neck malignances.…”
Section: Head and Neck Cancermentioning
confidence: 97%
“…Although, its application was quite restricted at the beginning (probably due to earlier technical difficulties in delivering heat on the tumor site) its beneficial effects were evident from early studies [106,107]. A great number of randomized phase II and III clinical trials utilizing hyperthermia have outlined its contribution in potentiating the efficiency of irradiation in treating breast [108], cervical [109], lung [110], head and neck [111], melanoma [112], gastrointestinal [113] and sarcoma cancers [114]. Furthermore, hyperthermia combined with several chemotherapeutic agents has been the subject of numerous phase II and III clinical trials.…”
Section: Hyperthermia In Clinical Practicementioning
confidence: 99%
“…In a systematic review and meta-analysis by Datta et al [13], a significant improvement in loco-regional control (LRC) was found for HNC patients, with an odds ratio of 2.92 (95% CI, 1.58-5.42) in favor of the combined treatment of hyperthermia plus radiation versus radiation [14]. In a phase III trial of Huilgol et al, hyperthermia-enhanced radiation treatment resulted in a higher complete response rate (79% versus 42% complete response) [15]. Given this ability of hyperthermia to enhance outcome without increasing toxicity [16], it seems reasonable to further study the combination of radiotherapy with hyperthermia for HNC.…”
Section: Introductionmentioning
confidence: 99%